(untitled) (Research, Society and Development, 2023)
Considering sexual violence as a complex, multifaceted, endemic and underreported public health problem, as well as its consequences for victims and society, in this study we look at the perpetrator of sexual violence in order to identify their characteristics based on national and international literature. The NCBI/PubMed, APA PsycInfo, CINAHL, Web of Science, Scopus and LILACS databases were used, including studies dealing with perpetrators of sexual violence published in Portuguese, English and Spanish, with no restriction on year of publication or methodological type. 46 studies were included in the review. The results show the profile of the man and woman author in relation to life cycle, marital status, education, skin color/ethnicity, work, if he/she suffered violence in childhood, if he used alcohol and drugs, as well as behaviors related to violence. Men and women who commit sexual violence against children in the family environment deserve special attention.